Coprecipitation Synthesis and Antimicrobial Effect Study of Europium Doped Spinel Manganese Ferrites Nanoparticles (MnEu0.1Fe1.9O4NPs) - Amina Chidouh; Tarek Tahraoui; Badra Barhouchi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Due to the high prevalence of micro-organisms resistant to conventional antimicrobials, the search for new antimicrobial drugs is underway, with nanoparticles being one of the options. This study reports for the first time the use of the coprecipitation method to synthesize europium (Eu) doped spinel manganese ferrites nanoparticles (MnEu0.1Fe1.9O4NPs). The purpose of this research is to determine the antimicrobial activity of MnEu0.1Fe1.9O4NPs. MnEu0.1Fe1.9O4NPs were analyzed using Fourier Transform Infrared Spectroscopy (FTIR), X Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-Ray Analysis (EDX) to determine their structure, size, morphology and elemental compositions. The antimicrobial activity of synthesized nanoparticles was evaluated qualitatively using a diffusion disc on agar, followed by minimum inhibitory concentrations (MIC) determination. The findings show that all tested strains were adversely affected by the examined NPs, where E. coli exhibited the highest sensitivity to NPs, followed by S. aureus. The NPs displayed a moderate level of anti-candida action. MnEu0.1Fe1.9O4NPs could be exploited in biomedical usages.